Developing New National Geodetic Reference Frame of Nepal (Journal on Geoinformatics, Nepal, 2025)
Geodetic reference frame is fundamental geodetic infrastructure required for positioning for surveying and mapping purposes. This paper presents a method to develop national level geodetic reference frame tied to global reference frame by utilizing the long-term GNSS observations. The key to realize a national reference frame is to transform Earth-Centered Earth-Fixed (ECEF) X, Y, and Z coordinates from International Terrestrial Reference Frame (ITRF) to national reference frame is by application of 14-Helmert transformation parameters. Initially, precise point positioning (PPP) provides the X, Y, and Z coordinates of reference stations with respect to ITRF, which in turn transformed to national geodetic reference frame. This paper discusses the development of 14-Helmert transformation parameter taking example of Nepal geodetic reference frame being built in near future.